Scars of the Battlefield: Analyzing the Psychological Impact of War on Women in Humayun Ahmed’s Jochna O Jononir Golpo - Sarkar, Sagor; Nabila, Sadiqa Jissan (International Journal of Language and Literary Studies, 2025)
The Bangladeshi Liberation War of 1971 is significantly celebrated and remembered as it marks the indelible history in the lives of the people who sacrificed their existence physically, emotionally, and mentally for the love of their motherland. In this context, Jochna O Jononir Golpo's (2004) is a widely read narrative as it offers a poignant depiction of the chaos of war from a bird's-eye perspective. The title translates to “The Story of Moonlight and Motherhood,” where the moon stands for a metaphor of beauty in Asian literature and shares a great similarity with motherhood embracing the world with the soft touch of the celestial body. The novel can be defined as a fictional autobiography as it delves into the author’s experiences alongside the central protagonists of the novel. The havoc of the war is reflected as Shahid’s wife and daughter walk out of the house with anger and are lost in the curfew of Dhaka city. The moment's intensity is demonstrated as Naimul, a calm student and the newlywed husband of Moriom, transforms into a ruthless soldier. Moriom’s eternal longing for her husband while filling her diaries with letters provides a flicker of hope for the soldiers at war. This paper aims to analyze how these characters’ traumas are amplified by their roles as women in a patriarchal society in the Bangladeshi Liberation War of 1971. Drawing on feminist theory, this paper analyses the emotional isolation, loss of identity, and societal negligence against women. Furthermore, the paper will also regain strength by exploring the resilience of these characters against the backdrop of a hostile environment amid war. The significance of this paper lies in acknowledging the pain and trauma endured by women during 1971 that are often silenced by the grand narratives of the political context.